PETA SELERA PASAR TEH DUNIA - Rohayati Suprihatini; E. Gumbira-Sa’id; Syamsul Ma’arif; Marimin Marimin (Jurnal Manajemen & Agribisnis, 2004)
In order to increase Indonesia tea export market share is required product improvement of Indonesian tea supply to serve the market preference in each world tea market region.   Research results showed that world tea market based on preference attibutes namely (1) tea type, (2) tea grade, and (3) organoleptic score apllying hierarchical cluster analysis, between-groups linkage method and Euclidean method can be classified in to five groups of tea markets.  Market Group-1 consist of Poland, Hungary, USA, and Canada; Market Group-2 consist of West Europe Region, Australia, Japan, East Europe in general, Turkey, North America Region, South America Region in general, and India; Market Group-3 consist of Pakistan, Afghanistan, Egypt, Malaysia, and Singapore; Market Group-4 consist of Iran and Middle East Region in general; and Market Group-5 consist of Iraq, Syria, and Russian Region especially Russian Federation.  Market Group-4 are markets typical having the highest preference due to only the best tea is accepted.    On the other hand, Market Group-1 are tea markets having lowest preference, while others Market Groups are in medium preference.